EFFECTIVE CACAO SOMATIC EMBRYO REGENERATION ON KINETIN SUPPLEMENTED DKW MEDIUM AND SOMACLONAL VARIATION ASSESSMENT USING SSRs MARKERS - Nur Ajijah; Rr. Sri Hartati; Rubiyo Rubiyo; Dewi Sukma; Sudarsono Sudarsono (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2016)
This study aimed to develop the cacao (Theobroma cacao L.) in vitro regeneration system through somatic embryogenesis on kinetin supplemented DKW medium and somaclonal variation assessment using SSR markers. Callus were initiated from basal petal and staminoid explants cultured on callus induction (CI) medium contained DKW basalt salts and kinetin:2,4-D ratios of 1:15.5, 1:7.8 or 1:3.9 and then transferred onto secondary callus growth (SCG) medium contained WPM basalt salts and kinetin:2,4-D ratios of 1:7.8 or 1:3.9. The calli were then subsequently transferred onto embryo development medium contained DKW basal salts with or without the addition of amino acids, adenine or activated charcoal for the formation of somatic embryos. Nine cacao genotypes were tested for their ability to develop somatic embryos. Results of this study indicated DKW medium supplemented with Kinetin in combination with 2,4-D effectively induced cacao somatic embryogenesis. The highest somatic embryos formation was abtained from kinetin:2,4-D ratio of 1:3.9 and 1:7.8 in CI and SCG medium respectively. Cacao genotype responses were highly explant type dependent. The developed method resulted in a high percentage of somatic embryo formation (5.6-66.7%), germination (50%) and plantlet conversion (65%) and a medium percentage of somaclonal variations based on SSRs marker analysis.